Chiral Dynamics : Theory and Experiment III. - Bernstein, Aron M. (Proceedings from the Institute for Nuclear Theory., 2001)
This book provides an authoritative, up to date, overview of the field of chiral dynamics, and also provides an excellent introduction to the field. The workshop is known for the interplay of theory and experiment and as a meeting place for most of the leading researchers in the field. Contents: Theoretical Chiral Dynamics (H Leutwyler); Experimental Chiral Dynamics (A Bernstein); CEBAF at Jefferson Lab, an Overview (B Mecking); Lorentz Invariant Baryon CHPT (T Becher); Sigma-Terms (J Gasser & M Sainio); Theory of Hadronic Atoms (A Rusetsky); Effective Field Theory in Nuclear Physics (M Savage.